The spatial ecology dynamics of groundwater quality: a case study of the urban environment, Yogyakarta City, Indonesia. Issue 1 (April 2021) - Nurroh, S; Gunawan, T; Kurniawan, A
Abstract: Ecological vulnerability assessment is essential to environmental degradation and resource management, particularly in the urban environment that given recent global warming concerns. In this study, we propose to evaluate the spatial ecology dynamics of groundwater quality with a typical ecologically in the urban environment, Yogyakarta city, as a case study. The proposed method is based on the definition of the Intergovernmental Panel on Climate Change and Water (IPCC VI) using software GeoDA 10.4. The results of the research study indicated the ecological spatial dynamics of quality groundwater in Yogyakarta City had variations in spatial correlation distribution. The overall result is 19% of the High-High (HH) classification areas appeared mainly between high concentration and the high population densities, where the economic activities have been developing rapidly. As well, 27% of the Low-Low (LL) classification areas appeared mainly between low concentration and the low population densities. The applied analysis indicates a spatial correlation between groundwater quality index and population densities index in the urban environment with positive autocorrelation. Based on result research that indicates the urgency of applying the sanitation facilities to convince local society for anticipating climate change regarding groundwater quality.